2021
DOI: 10.3389/phrs.2021.1603979
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perceptions, Knowledge and Behaviors of General and High-Risk Adult Populations Towards COVID-19: A Systematic Scoping Review

Abstract: Objectives: The COVID-19 pandemic represents a major crisis for governments and populations. The public’s risk perceptions, knowledge, and behaviors are key factors that play a vital role in the transmission of infectious diseases. Our scoping review aims to map the early evidence on risk perceptions, knowledge, and behaviors of general and high-risk adult populations towards COVID-19.Methods: A systematic scoping review was conducted of peer-reviewed articles in five databases on studies conducted during the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 80 publications
(321 reference statements)
3
14
0
Order By: Relevance
“…Furthermore, married people (compared to people who are single, widowed, or divorced) have higher neighborhood-based perceived COVID-19 risk, while people with a high monthly household income (>HKD 40,000, compared to the middle and low monthly household income group) have a lower neighborhood-based perceived COVID-19 risk. The results are consistent with the findings of previous studies, which found that educational status, income level, and marital status have strong associations with people’s perceived COVID-19 risk [ 45 , 46 , 47 , 48 ].…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, married people (compared to people who are single, widowed, or divorced) have higher neighborhood-based perceived COVID-19 risk, while people with a high monthly household income (>HKD 40,000, compared to the middle and low monthly household income group) have a lower neighborhood-based perceived COVID-19 risk. The results are consistent with the findings of previous studies, which found that educational status, income level, and marital status have strong associations with people’s perceived COVID-19 risk [ 45 , 46 , 47 , 48 ].…”
Section: Resultssupporting
confidence: 92%
“…In line with the abundant literature on health behaviors, our findings confirmed: (i) the positive relationship provided by HBM theory between perceptions of SARS-CoV-2 risk (vulnerability and severity) and vaccination intention, through fear of COVID-19 [20,[47][48][49][50][51][52][53]; (ii) the positive relationship between subjective norms and both trust in science and vaccination intention [124,125]; (iii) that trust in science plays a crucial role in predicting vaccination intention (11,67,68,79,80,83,84]. The results also provided indications about a positive relationship between subjective norms and fear of COVID-19, and a possible full mediation role of trust in science in the relationships between determinants of both TPA and HBM, fear of COVID-19, and vaccination intention.…”
Section: Discussionsupporting
confidence: 88%
“…From the review of the HBM literature, several confirmations emerge on the positive relationship between perceptions of SARS-CoV-2 risk (mostly concerning vulnerability and severity) and fear of COVID-19 [ 48 , 49 , 50 , 51 , 52 ], and on the positive relationship between fear of COVID-19 and vaccination intention [ 20 , 47 , 53 ]. Following these relationships, we can formulate several hypotheses (see Figure 1 ): Hp 1a and Hp 1b: a higher risk perception (higher vulnerability and severity) will be positively related to fear of COVID-19; Hp 2a: a higher fear of COVID-19 will be associated with a lower intention to receive the booster; Hp 2b: a higher fear of COVID-19 will be associated with lower Trust in Science.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Due to an increase in vaccine refusal and a lack of widely used new treatment options, the best way to control the spread of infections is to adapt COVID-19 protection behaviors. Owing to the apparent predictive effect of gender, age, and education level on protective behaviors, speci c plans should be created to strengthen COVID-19 preventive behaviors.In various countries, the level of knowledge is important in adapting to protective behaviors(Clavel et al, 2021). It was also determined that the frequency of obtaining information and having correct knowledge about COVID-19 were positive predictors of protective behavior in this study.…”
mentioning
confidence: 85%